Pengaruh Pemberian Ekstrak Kunyit Putih (Curcuma zedoaria Rosc.) terhadap Kadar Malondialdehid (MDA) Tikus Putih (Rattus norvegicus) yang Terpapar Asap Rokok - Putra, I Made Agus Sunadi; Suwantara, I Putu Tangkas; Sasadara, Maria Malida Vernandes; Udayani, Ni Nyoman Wahyu (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2025)
Cigarette smoke generates free radicals that induce oxidative stress and damage various biomolecules in the body. An increase in malondialdehyde (MDA) levels is a key marker of oxidative stress. The body’s antioxidant mechanisms rely on compounds capable of neutralizing free radicals. White turmeric (Curcuma zedoaria Rosc.) contains antioxidant compounds predicted to prevent oxidative damage, though its in vivo potential remains to be proven. This study aimed to evaluate the effect of white turmeric ethanol extract on MDA levels in male Wistar rats (Rattus novergicus) exposed to cigarette smoke. A post-test only control group design was employed. The rats were divided into five groups: healthy control (P1), smoke-exposed control (P2), extract-treated groups receiving 100 mg/kgBW (P3) and 200 mg/kgBW (P4), and a positive control group receiving vitamin C (P5). Cigarette smoke exposure was administered for 14 days, and blood samples were collected from the orbital vein on day 15. MDA levels were measured using the ELISA method. The mean MDA levels (mmol/ml) for P1 to P5 were 0.118, 0.121, 0.094, 0.059, and 0.089, respectively. ANOVA and post hoc LSD tests (α = 0.05) showed a significant difference between P2 and P4 (p < 0.05), while no significant differences were found between P3, P4, and P5. In conclusion, white turmeric extract at 200 mg/kgBW significantly reduced MDA levels and demonstrated antioxidant activity comparable to that of vitamin C.